Perbaikan Mutu Berkelanjutan dan Standar Mutu - Syukri, Makmur; Muammar, Muammar (VISA: Journal of Vision and Ideas, 2024)
This research aims to analyze the improvement of sustainable quality and quality standards at the Madrasah Aliyah in Langkat. The study uses a qualitative approach with descriptive research. Data was collected through interviews, observations, and documentation. The subjects of this study are the school principal, teachers, and students of Madrasah Aliyah in Langkat. The results show that the improvement of sustainable quality and quality standards at the Madrasah Aliyah in Langkat is achieved by planning innovative and distinctive programs to enhance the quality of the educational process and the quality of graduates, such as grouping language classes, Olympiad classes, research classes, acceleration classes, improving infrastructure quality, creating a conducive environment, developing extracurricular religious curriculum, trilingual speeches, arts and culture, and sports activities, all of which aim to improve the quality of graduates as the output of the education process carried out at the Madrasah.